PENGARUH KEBIJAKAN DIVIDEN, INTENSITAS MODAL, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Santika, Afqia; Siarwi, Siarwi (Jurnal Nusa Akuntansi, 2025)
This study aims to empirically test whether there is an influence between dividend policy, capital intensity, managerial ownership, and institutional ownership on tax aggressiveness in Property and Real Estate sector companies in Indonesia. The data source used is secondary obtained from the Indonesia Stock Exchange, by taking annual reports and financial reports in the 2019-2023 period and selected using purposive sampling. The sample of this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. The population used in this study were 8 companies with a total of 40 data observations. This study uses four variables, namely Dividend Policy, Capital Intensity, Managerial Ownership, and Institutional Ownership as independent variables while the dependent variable is Tax Aggressiveness. The test used is panel data regression analysis using the Eviews 12 program. The results of this study indicate that Dividend Policy, Capital Intensity, and Managerial Ownership, simultaneously affect Tax Aggressiveness, while Institutional Ownership has no effect on tax aggressiveness.